Deviations of Artificial Intelligence in the Technological Arts: Algorithms, Bodies, Affections, and Other Materialities Towards the Dismantling of the Myth of Novelty - Adler, Jazmín (Eikón / Imago, 2024)
The article analyzes a set of contemporary works that from the convergences of art and technologies explores the field of artificial intelligence, through the confluence of different kinds of materialities, both physical and virtual. Nevertheless, the cognitive capacities of the computational systems involved in these projects are not circumscribed to the role of complicity with respect to the phenomenon of algorithmic governmentality, but implement different tactics of deviation from the instrumental uses of technologies. Those strategies are aimed at disarticulating their hegemonic functions of control over bodies and affects, or at transgressing the expected efficiency of artificial intelligences. Through the perspective of neomaterialism, we argue that the selected works crystallize certain tensions identified here as authorial dispute, generative condition and transgressions towards physical materiality, which are also present in other projects developed since the middle of the last century unrelated to artificial intelligence. The article concludes that these categories allow us to demystify the radical novelty that artificial intelligence implies for the history of art, while they incite critical re-readings of its narratives in order to link the history of mainstream contemporary art with the technological art scene.